Direct-light-triggered Thyristor Valves and Its Control System in Static Var Compensator(SVC) - YANG Lei; TAN Shengwu; ZHANG Dinghua; ZHOU Jing (Kongzhi Yu Xinxi Jishu)
This paper introduces a new type of semiconductor device--the characteristics of direct light-triggered thyristors and its realization principle. It is highlighted direct- light-triggered thyristor valves and features, functions, composition, control theory of the control system in actual applications of static var compensator.